Crop protection project to minimize residues - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Internationally there is increasing concern with regard to pesticide residues in foodstuff, and Kenya, as a major horticultural exporter, is keen to preserve its markets. Government departments and exporters, through their trade associations, are...